Revealing a novel Decorin-expressing tumor stromal subset in hepatocellular carcinoma via integrative analysis single-cell RNA sequencing - Chi Hsiao; Wen-Chieh Liao; Ju-Pi Li; Yu-Cheng Chou; Yu-Lun Chou; Jeng-Rong Lin; Chia-Hua Chen; Chiung-Hui Liu (Cancer Cell International)
Abstract Hepatocellular carcinoma (HCC) remains a leading cause of cancer-related mortality, emphasizing the need for novel therapeutic strategies. Decorin (DCN), a chondroitin sulfate proteoglycan (CSPG), has been proposed as a tumor suppressor, yet its precise role in HCC and the tumor microenvironment (TME) remains underexplored. Through integrated analyses of bulk RNA and single-cell RNA sequencing datasets, we identified a distinct tumor stromal subset highly expressing DCN and associated chondroitin sulfate (CS) synthases. Our findings revealed that DCN expression is significantly downregulated in HCC tissue, but upregulated in peri-tumor stroma, where it correlates with better prognosis and reduced capsular invasion. Western blot analysis demonstrated that CS-DCN, the glycosylated form of DCN, plays a dominant role in this context. Single-cell clustering analysis identified a unique stromal subset in HCC characterized by elevated expression of DCN, CSPGs, and CS synthases, associated with extracellular matrix (ECM) remodeling and protective barrier functions. A six-gene DCN-associated signature derived from this subset, including DCN, BGN, SRPX, CHSY3, CHST3, and CHPF, was validated as a prognostic marker for HCC. Furthermore, functional assays demonstrated that CS-DCN significantly inhibited HCC cell proliferation and invasion. Our study highlights the critical role of DCN in HCC TME and provides insights into its therapeutic potential. Modulating CSPG pathways, particularly on CS-DCN-expressing stromal cells, may offer a promising approach for improving HCC treatment and patient outcomes.